2015
DOI: 10.1007/s12185-015-1763-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics and prognostic factors for angioimmunoblastic T-cell lymphoma

Abstract: Angioimmunoblastic T-cell lymphoma (AITL) is a distinct peripheral T-cell lymphoma entity exhibiting peculiar clinical features and poor prognosis. Its clinical characteristics and prognostic factors are not well established. To clarify the clinical characteristics and prognostic features of AITL, we conducted a multicenter, retrospective study. Fifty-six patients were enrolled. The median patient age was 68 years. Immunohistochemical examinations of tumor cells showed positivity for CD10 and T-cell markers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Thrombocytopenia (<150 × 10 9 /mm 3 ) was detected in about 33% of our cases, irrespective of age. Previous reports documented thrombocytopenia in 20%‐40% of patients with AITL; moreover, in a fraction of those patients, thrombocytopenia was related to immune thrombocytopenic purpura . Previous studies also reported an association between thrombocytopenia and poor OS and PFS…”
Section: Discussionmentioning
confidence: 91%
“…Thrombocytopenia (<150 × 10 9 /mm 3 ) was detected in about 33% of our cases, irrespective of age. Previous reports documented thrombocytopenia in 20%‐40% of patients with AITL; moreover, in a fraction of those patients, thrombocytopenia was related to immune thrombocytopenic purpura . Previous studies also reported an association between thrombocytopenia and poor OS and PFS…”
Section: Discussionmentioning
confidence: 91%
“…However, IPI was not predictive of survival in AITL patients, and a high PIT score was not associated with a good outcome. 2 Histone deacetylase (HDAC) inhibitors are a new class of antitumor agent that is currently undergoing intensive preclinical and clinical testing. Depsipeptides, a member of the 26 Thus, HDAC inhibitors may be useful for treating patients with AITL or other types of cancer in which p53 plays a role, while the efficacy of HDAC class III inhibitors for AITL has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Angioimmunoblastic T-cell lymphoma (AITL) is one of the most common forms of peripheral T-cell lymphoma (PTCL) and accounts for approximately 15-20 % of PTCL and 1-2 % of non-Hodgkin's lymphoma. 1,2 AITL generally affects the elderly population, and the median age of patients is greater than 60 y with a slighter greater preponderance in males. AITL is manifested mostly after exposure to medications such as specially antibiotics, viral, bacterial, fungal infection, or an allergic reaction suggesting abnormalities in immune regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 5 ] Several studies have reported 5-year overall survival (OS) rate of AITL patients ranging from 33% to 48% and 5-year progression-free survival (PFS) rate ranging from 18% to 25%. [ 2 , 4 7 ] The International Prognostic Index (IPI) and the prognostic index for PTCL (PIT), have been widely used in patients with various types of non-Hodgkin lymphoma (NHL). However, the application of IPI and PIT scores in AITL are still controversial.…”
Section: Introductionmentioning
confidence: 99%